Vocal health and hygiene among classroom teachers - Burney, Kristina (My University, 2026)
The voice is the choral musician’s instrument, and it is just as surely the primary instrument of every teacher, whatever the subject. Yet it is remarkably vulnerable: an estimated 17.9 million adults in the United States report problems with their voice (National Institute on Deafness and Other Communication Disorders [NIDCD], 2016), and teachers are markedly overrepresented, with prevalence reported to be as high as 44% (Baghban et al., 2025). I found this disturbing. I began researching the most common causes and risks of vocal problems among teachers, as well as ways to improve the overall health and hygiene of our voices. For my project, I developed and presented a professional development session on vocal health and hygiene for teachers for our school district at the district-wide Professional Development Day. Attendance was lower than I expected, as many teachers were in required subject-area meetings. Therefore, if I were to do this project again, I would focus more on individual departments or site presentations rather than presenting it alongside so many competing required sessions.
Keywords: Vocal health; Classroom teachers